Edukasi Pengenalan Bahaya Kanker Payudara (Ca.Mammae) di Puskesmas Maccini Sawah - Erna Kasim; Nurbaiti Nurbaiti; Ekayanti Hafidah Ahmad; Asra Hatlah; Desriani Desriani (Jurnal DIKMAS, 2021)
Breast cancer is the first cancer in Indonesia and is one of the first contributors to death caused by cancer. Breast cancer reached 68,858 cases out of a total of 396,914 new cases in Indonesia. Unfortunately, around 70% of cases are detected too late and are at an advanced stage. The impact for Indonesia is of course not only an economic double burden but also the level of public health. Therefore, there is a need for pro-active efforts by academics to help reduce breast cancer cases. One way is through health promotion by educating people about the dangers of breast cancer. Group counseling method. Counseling participants with a population of 35 people. The media used were power points and leaflets, which lasted approximately 50 minutes. The results of community service show that after education, 77.5% of people can answer questions about breast cancer well. And there is enthusiasm in asking questions in detail. Counseling participants can understand and increase their insight into the dangers of breast cancer. Counseling can be done at a later time.